Biomarkers of Neurodegeneration in Autoimmune-Mediated Encephalitis - Körtvelyessy, Peter; Prüss, Harald; Thurner, Lorenz; Maetzler, Walter; Vittore-Welliong, Deborah; Schultze-Amberger, Jörg; Heinze, Hans-Jochen; Reinhold, Dirk; Leypoldt, Frank; Schreiber, Stephan; Bittner, Daniel (Frontiers in Neurology, 2018)
Progranulin (PGRN), Total-Tau (t-tau), and Neurofilament light chain (NfL) are well known biomarkers of neurodegeneration. The objective of the present study was to investigate whether these parameters represent also biomarkers in autoimmune-mediated Encephalitis (AE) and may give us insights into the pathomechanisms of AE. We retrospectively examined the concentration of PGRN in the cerebrospinal fluid (CSF) and serum of 38 patients suffering from AE in acute phase and/or under treatment. This AE cohort comprises patients with autoantibodies against: NMDAR (n = 18 patients), Caspr2 (n = 8), Lgi-1 (n = 10), GABAB(R) (n = 1), and AMPAR (n = 1). Additionally, the concentrations of NfL (n = 25) and t-tau (n = 13) in CSF were measured when possible. Follow up data including MRI were available in 13 patients. Several age-matched cohorts with neurological diseases besides neuroinflammation or neurodegeneration served as control groups. We observed that PGRN was significantly elevated in the CSF of patients with NMDAR-AE in the acute phase, but normalized at follow up under treatment (p < 0.01). In the CSF of other patients with AE PGRN was in the range of the CSF levels of control groups. T-tau was highly elevated in the CSF of patients with temporal FLAIR-signal in the MRI and in patients developing a hippocampal sclerosis. NfL was exceptionally high initially in Patients with AE with a paraneoplastic or parainfectious cause and also normalized under treatment. The normalizations of all biomarkers were mirrored in an improvement on the modified Rankin scale. The data suggest that the concentration of PGRN in CSF might be a biomarker for acute NMDAR-AE. Pathological high t-tau levels may indicate a risk for hippocampal sclerosis. The biomarker properties of NfL remain unclear since the levels decrease under treatment, but it could not predict severity of disease in this small cohort. According to our results, we recommend to measure in clinical practice PGRN and t-tau in the CSF of patients with AE.